Effects of taxes financing decisions and firm value in Nigeria - Olatundun Adelegan (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
The study sets out to measure how the taxation of dividend and debt affects firm value. Tax hypothesis predicts that firm value is negatively related to dividends and positively related to debt. The study covered 1197 firm-year observations of manufacturing firms in Nigeria from 1984 to 2000. To achieve the objective, the study estimated the model on the average values for each firm and tested for industry effects using the ordinary least square (OLS) method. We found the opposite of tax hypotheses predictions from the regression results. We hypothesized that the relationship between dividends, debt and firm value will be affected by the size of the firm. We therefore partitioned the firms into two on the basis of size measured as market capitalization. We estimated separate equations for each sub-sample and found positive relationship between dividend and firm value and negative relationship between debt and firm value in both small-sized firms and big firms? sub-sample. The study concludes that dividend and debt convey information about profitability of firms. This information about firms? profitability obscures any tax effect of financing decisions. However, we found that earnings and investment are key determinants of firm value in Nigeria.
Keywords: 330